2010
DOI: 10.1165/rcmb.2009-0031oc
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial–Mesenchymal Transition in Bleomycin-Induced Pulmonary Fibrosis

Abstract: The pathological hallmark lesions in idiopathic pulmonary fibrosis are the fibroblastic foci, in which fibroblasts are thought to be involved in the tissue remodeling, matrix deposition, and cross-talk with alveolar epithelium. Recent evidence indicates that some fibroblasts in fibrosis may be derived from bone marrow progenitors as well as from epithelial cells through epithelial-mesenchymal transition. To evaluate whether endothelial cells could represent an additional source for fibroblasts, bleomycin-induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
317
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 366 publications
(331 citation statements)
references
References 54 publications
11
317
0
3
Order By: Relevance
“…The direct treatment of endothelial cells with BLM in vitro has been shown to induce the secretion of certain profibrotic mediators (7,8), but little is known about the effects of BLM on endothelial cells in vivo. Moreover, recent studies have suggested that a process known as the endothelial-to-mesenchymal transition (EndMT) may be activated during fibrotic processes, creating fibroblast-like cells that contribute to excess collagen production (8,9). Finally, the activation of endothelial cells may contribute to prolonged tissue injury by promoting a proinflammatory environment.…”
mentioning
confidence: 99%
“…The direct treatment of endothelial cells with BLM in vitro has been shown to induce the secretion of certain profibrotic mediators (7,8), but little is known about the effects of BLM on endothelial cells in vivo. Moreover, recent studies have suggested that a process known as the endothelial-to-mesenchymal transition (EndMT) may be activated during fibrotic processes, creating fibroblast-like cells that contribute to excess collagen production (8,9). Finally, the activation of endothelial cells may contribute to prolonged tissue injury by promoting a proinflammatory environment.…”
mentioning
confidence: 99%
“…In SSc, targeting of the TGF␤-dependent EndoMT process via small-molecule kinase inhibitors, such as imatinib mesylate and rottlerin, might represent a promising treatment for both tissue fibrosis and vasculopathy, the two major aspects of the disease. Indeed, EndoMT might substantially contribute not only to pathologic vascular remodeling in SSc, but also to dermal and internal organ fibrosis, as has recently been observed in experimental models of kidney and lung fibrosis (13,15). Previous studies have shown that blocking of c-Abl with imatinib mesylate could prevent, or induce regression of, dermal fibrosis in different mouse models of SSc and could attenuate bleomycin-induced pulmonary fibrosis in mice (24)(25)(26).…”
Section: New Insights Into Endomt: C-abl Protein Kinase C␦ and Smalmentioning
confidence: 83%
“…EndoMT is a phenomenon that is reported to occur during embryonic cardiovascular development and also is reported to play an important role during several pathologic conditions, including cardiac, pulmonary, and renal fibrosis, carcinoma-associated interstitial fibrosis, and vascular pathologies (9,(11)(12)(13)(14)(15)(16). Indeed, recent evidence has shown that a substantial proportion of myofibroblasts arise from ECs via EndoMT in experimental renal fibrosis and bleomycin-induced pulmonary fibrosis in mice (13,15).…”
Section: The Origins Of Myofibroblasts: Endothelialmesenchymal Transimentioning
confidence: 99%
See 1 more Smart Citation
“…Констатация сочетания фиброза и кальцифика ции, понятная лишь с позиций гистогенетической общности мезенхимальных предшественников со единительной и костной тканей, изменилась в конце 1990 х годов при выявлении биохимических и моле кулярных звеньев патогенеза фиброзирующих и ос сифицирующих заболеваний в целом [29][30][31], в т. ч. и системы органов дыхания [11,[32][33][34], а также таких клинически значимых заболеваний, как ге теротопическая оссификация у обездвиженных па циентов с ожогами, обширными травмами скелета, черепно мозговыми или спинальными травма ми [35][36][37] и прогрессирующая оссифицирущая фибродисплазия [38][39][40]. С этого времени в патоге нетический каскад стали включаться про и проти вовоспалительные, ростовые факторы и рецепторы к ним, молекулы адгезии, сигнальной трансдукции, регуляторы трансляции (активирующие и ингибиру ющие).…”
Section: заметки из практикиunclassified